Interpretation of Income and Expense in Accounting - A.Z.Avlokulov; D.A.Turumova, (Researchparks Publishing, 2023)
In this article discussed the concepts of income and expenses, their recognition and assessment according to international standards. Based on the results of the study, were developed recommendations to improve the information support of income and expenses.